The Role of YouTube Children's Educational Videos in Enhancing Early Childhood English Language Proficiency: An Investigation of Parental Perceptions - Osias Kit T. Kilag; Marsha Heyrosa-Malbas; Mervin T. Arcillo; Merlinda C. Barcena (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study explored the use of YouTube children's educational videos to enhance early childhood English language proficiency. The study utilized a qualitative research design, and data were collected through semi-structured interviews with 10 parents of preschool-aged children. The findings of the study revealed that parents used a variety of YouTube children's educational videos to enhance their children's English language proficiency, including videos that taught basic English vocabulary, songs, nursery rhymes, grammar, and sentence structures. Participants also identified perceived benefits and drawbacks of using YouTube children's educational videos, such as improvements in vocabulary and grammar skills, exposure to the English language, and concerns about addiction to watching videos, exposure to inappropriate content, and quality and accuracy issues. Moreover, parents perceived YouTube children's educational videos to be effective in enhancing their children's English language skills, and various factors influenced their decision to use such videos, such as convenience, affordability, variety of content, and fun and engaging learning. The study suggests that YouTube children's educational videos can be a useful tool to enhance early childhood English language proficiency. However, parents need to be mindful of the potential drawbacks associated with their use, such as inappropriate content and addiction. The study also contributes to the existing literature on the use of technology in early childhood education and provides insights into parents' perspectives on YouTube children's educational videos.